Night of Beginnings : A Passover Haggadah - Falk, Marcia (Book collections on Project MUSE., 2022)
Night of Beginnings is a groundbreaking new haggadah for the Passover seder from acclaimed poet, translator, and liturgist Marcia Falk, beautifully designed and illustrated with original color drawings by the author.